P094 Chlamydia trachomatis (CT) positivity rate at 2 week Neisseria gonorrhoeae (NG) test of cure (TOC). (30th June 2016) - Girometti, Nicolo; Scott, Joseph; Rhodes, Kimberly; McOwan, Alan; Nwokolo, Nneka; Whitlock, Gary
Abstract : Background/introduction: Whilst guidelines recommend NG TOC 2 weeks after treatment, there is little data on the optimum time to perform a TOC for CT in those for whom this is indicated. Current BASHH guidelines recommend deferring TOC for at least 3 weeks after treatment because residual chlamydial DNA may persist. Aim(s)/objectives: Patients who are treated for NG and CT co-infection re-attending for subsequent NG TOC are tested for both infections by NAAT providing the opportunity to evaluate the CT positivity rate at re-attendance. Methods: A retrospective case review of co-infected GC/CT positive (analysed with Cepheid GeneXpert) patients tested in aLondon sexual health clinic over 12 consecutive months wasperformed. TOC details were evaluated, and appropriate antibiotic treatment according to BASHH guidelines was assessed. Results: 480 patients tested positive for both infections and 132 attended for TOC within 21 days of treatment (median 15 days, IQR 14–17). Of these 131 were male, of whom 126 MSM; median age was 35 y and median number of sexual partners in previous 3 months was 5. Site of CT infection was rectal (94), urethral (49), throat (11), vulvovaginal (1). At TOC, 6 (4.5%) had a persistent positive CT NAAT: rectum (3), urethra (3). One patient with persistent rectal CT had received treatment with azithromycin; the other 5 received BASHH preferred treatment. By comparison, 3 (2.3%) had a positive NG NAAT at TOC. Discussion: CT positivity 15 days after treatment is low, suggesting that TOC at 2 weeks may be a possible management strategy.